Woody cover and pasture within the surrounding matrix drive puma (Puma concolor) occupancy in agroecosystems of the Argentine Dry Chaco - Nanni, Ana Sofía; Regolin, André Luis; Fernandez, Pedro David; Giordano, Anthony J.; Martello, Felipe; Bailey, Larissa Lynn; Lucherini, Mauro (Elsevier, 2025)
The puma (Puma concolor) is distributed over most vegetation types and elevation ranges, but is still sensitive to habitat loss and human persecution. Due to its large spatial requirements, pumas must persist in human-modified landscapes, where vegetation cover and prey availability can limit its occurrence. Few studies have assessed the suite of factors that may influence carnivore persistence in deforestation frontiers such as the Dry Chaco. We explored the influence of landscape structure, native prey availability, and local anthropogenic proxies on puma occupancy in Argentine Dry Chaco agroecosystems through a single-season occupancy framework based on camera-trap surveys. We used the results to predict puma occupancy for the ecoregion. Woody cover and the proportion of pasture within the surrounding matrix influenced puma occupancy: in areas with moderate to little woody cover, puma occupancy was negatively influenced by the proportion of pasture relative to cropland. Predicted puma occupancy probability was very high throughout half of the ecoregion. Our results corroborate the landscape-scale importance of woody cover for the puma in the Dry Chaco. However, the negative relation between puma occupancy and pasture dominance in areas with little woody cover could be suggesting potential negative interactions with humans, or seasonal variations in environmental condictions and resource availability that should be further explored.